Personalized Dietary Self-Management and Its Influence on Disease Progression in Chronic Hepatitis B - Yuan-Yuan Wang; Yu-Qian Yao; Yue Sun; Xiang-Yun Qian (Journal of Nutrition and Metabolism, 2025)
Conclusion: The results of this study showed the benefit of the vegetable oil for CHB patients when it appropriately served as the way of energy intake, during the patients’ treatment period. A larger scale of this personalized dietary self-management education should be permitted for further assessment.